Teaching English Speaking Strategies in COVID-19 Era for English Department Students at UKI Toraja - Rony La'biran; Resnita Dewi (LPPM UKI Toraja, 2021)
The purpose of this study is to find out The Teaching Strategies in Learning Speaking Skill in Covid-19 era. In analyzing the data of this research, the researcher employed qualitative method to analyze data using theories from Miles and Huberman. The subjects of this study were the speaking lecturers at English Study Program of FKIP UKI Toraja. The data of this research was collected by interview. The result of the research shows that there are 4 (four) strategies in teaching English speaking in covid-19 era are Self-study Strategy, Use of YouTube application, Use of WhatsApp application, Question and Answer strategy.